Note on an Early Physiological Index of ESP: John E. Purdon’s Observations of Synchronous Pulse Rates - Alvarado, Carlos S. (Journal of Scientific Exploration, 2015)
<span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The purpose of this note is to rescue from oblivion the nineteenth-century researches of physician John E. Purdon with measures of pulse rate synchrony between two persons. This was done using a sphygmograph, an instrument that measured pulse and provided graphic tracings on paper. According to Purdon he found some persons reproduced the tracings of others in conditions he considered to imply a telepathic transfer. Purdon speculated that one person produced emissions of nervous force that were propagated to others via the ether. While this research may be criticized from the point of view of modern research standards, it is presented here as an interesting and generally unknown early instrumental study of the concept of the detection of ESP via a physiological response.